THE ROLE OF BRAND IMAGE IN MEDIATION OF THE RELATIONSHIP OF CELEBRITY ENDORSER WITH THE BRAND EQUITY OF TRAVELOKA - Kurniawan, Ryan; Kristadi, Azzuar, Bahyu; Agustinus, Riki; Fauzia, Clara; Mahardika, Rafly; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
In this study, researchers want to know consumer opinion on celebrity endorser, brand image, and brand equity of Traveloka, and for knowing the role of brand image in relationship celebrity endorser mediation and brand equity of the Traveloka. the method used is descriptive and verification research. According to the analysis that has been done, it can be concluded that the hypothesis submitted by the writer that is celebrity endorser has a relation with brand equity, it can be accepted that celebrity endorser have relations with brand equity. The writer suggest that celebrity endorser election of Traveloka should be maintained.